George Washington's Enforcers : Policing the Continental Army. - Ward, Harry M. (Southern Illinois University Press, 2009)
A well-disciplined army was vital to win American independence, but policing soldiers during the Revolution presented challenges. George Washington's Enforcers: Policing the Continental Army examines how justice was left to the overlapping duties of special army personnel and how an improvised police force imposed rules and regulations on the common soldier. Historian Harry M. Ward describes these methods of police enforcement, emphasizing the brutality experienced by the enlisted men who were punished severely for even light transgressions. This volume explores the influen.